On the Privacy of National Contact Tracing COVID-19 Applications: The Coronavírus-SUS Case - Nobre, Jéferson C.; Soares, Laura R.; Huaytalla, Briggette O. R.; S. Júnior, Elvandi da; Granville, Lisandro Z. (Anais da Escola Regional de Redes de Computadores (ERRC), 2021)
The COVID-19 pandemic, caused by the quick dissemination of the SARS-CoV-2 vírus, deeply impacted the world. The use of digital technologies has been crucial in the effort to control it, and, among others, digital contact tracing (DCT) applications stood out. DCT was successfully employed to face other infectious diseases in the past. However, its use poses several privacy concerns due to the sensitiveness of the data it handles. These concerns are even more relevant when considering nationwide implementations, despite several countries having data protection regulations in place. This article analyzes the privacy features in national DCT COVID-19 applications and their overall adhesion. As a case study, we discuss in more depth Brazil's application, Coronavírus-SUS, since Brazil is one of the most impacted countries by the pandemic. Finally, as we believe DCT will remain relevant in health-related tasks, we present key research challenges.